Emotional dependence and attitudes towards spousal violence among women victims of violence in the district of Pallanchacra in the department of Cerro de Pasco, 2015 - Espinoza Meza, Alex Jhonatan (2016)
In this research the relationship between emotional dependence and Attitudes towards domestic violence in battered women Pallanchacra district in the department of Cerro de Pasco in the 2015 study, a census sample of 114 women aged 18 to 60 years is performed. To measure these two variables two scales of Likert was used to measure the emotional Unit questionnaire by Lemos and Londoño (2007) was employed as the measurement of attitudes towards domestic violence, the questionnaire Chuquimajo was used (2000) Attitudes towards violence of women (VM), in both a test pilot was used to see its impact on the population. It was found that there is a relationship between emotional dependence and favorable attitudes toward domestic violence (r = 0.833; p = 0.000), which differs with the attitudes of indifference showing battered women, likewise there is no evidence that some of the factors emotional dependence influence directly in attitudes towards domestic violence, however if high levels of emotional dependence and neutral trends favoring or use of violence as a means of correction evidence. Finally both marital status and level of primary education at high levels in both study variables, which are considered risk factors that increase the incidence of battered women.